Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0885328215613886
|View full text |Cite
|
Sign up to set email alerts
|

Physical preparation of alginate/chitosan polyelectrolyte complexes for biomedical applications

Abstract: Polyelectrolyte complexes represent a special class of polymeric compounds consisting of stoichiometric equivalents of oppositely charged polyions interacting together spontaneously to yield a complex in different forms. The present study aimed at preparing coacervates of alginate and chitosan polymers ready for casting as wound dressing films. This was based on controlling the pH of solutions and the reactions speed through controlling the rate of mixing of the polymers solutions together without using any wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…From a delivery standpoint, bulk and hydrogel‐like coacervate‐based materials are typically the most useful in circumstances that allow for bolus‐style delivery (i.e., direct application or injection of the material to the site of interest). For example, coacervate‐based hydrogels composed of alginate and chitosan were shown to enhance the proliferation of cells in vitro while accelerating healing efficiency and wound closure in a rat model . In another series of reports, the cationic polymer poly(ethylene argininylaspartate diglyceride) (PEAD) was used in concert with the glycosaminoglycan heparin to form coacervate‐based delivery vehicles that take advantage of the strong binding affinity between heparin and various growth factors to enable cargo encapsulation and protection.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a delivery standpoint, bulk and hydrogel‐like coacervate‐based materials are typically the most useful in circumstances that allow for bolus‐style delivery (i.e., direct application or injection of the material to the site of interest). For example, coacervate‐based hydrogels composed of alginate and chitosan were shown to enhance the proliferation of cells in vitro while accelerating healing efficiency and wound closure in a rat model . In another series of reports, the cationic polymer poly(ethylene argininylaspartate diglyceride) (PEAD) was used in concert with the glycosaminoglycan heparin to form coacervate‐based delivery vehicles that take advantage of the strong binding affinity between heparin and various growth factors to enable cargo encapsulation and protection.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, coacervate-based hydrogels composed of alginate and chitosan were shown to enhance the proliferation of cells in vitro while accelerating healing efficiency and wound closure in a rat model. 213 In another series of reports, the cationic polymer poly(ethylene argininylaspartate diglyceride) (PEAD) was used in concert with the glycosaminoglycan heparin to form coacervate-based delivery vehicles that take advantage of the strong binding affinity between heparin and various growth factors to enable cargo encapsulation and protection. Applications included the use of heparin-binding epidermal growth factorlike growth factor (HB-EGF) to accelerate wound healing, 197 fibroblast growth factor-2 (FGF2) to enhance angiogenesis in both surface wounds and after myocardial infarction 76,78 (Figure 8(a)), stromal cell-derived factor (SDF)-1a for vascular regeneration, 108 bone morphogenetic protein-2 for stem cell differentiation and bone formation, 214 nerve growth factor (NGF) for nerve regeneration, 110 and the anti-inflammatory cytokine interleukin-10 (IL-10).…”
Section: Delivery Platformsmentioning
confidence: 99%
“…It is the example of the work of Liao et al [32] that has demonstrated that the production of a PEC fibre of alginatechitosan can be an effective drug carrier with potential advantages of high loading level and high encapsulation efficiency. Another study that demonstrated the biomedical potential of these materials was the one from Alsharabasy et al [30], which demonstrated the preparation of a high quality alginate chitosan complex in the form of a hydrogel film that stimulates cell proliferation and wound closure, demonstrating the potentiality of these materials for wound healing applications.…”
Section: 23polyelectrolyte Complexesmentioning
confidence: 99%
“…Moreover, the capability to absorb water is excellent. It can absorb 20 times the volume of water compared to its volume and 5 to 7 times more than the traditional gauze . Besides, calcium alginate dressing can exchange calcium ions when applied to the wounds, which contributes to hemostasis .…”
Section: Introductionmentioning
confidence: 99%